2022
DOI: 10.12688/wellcomeopenres.18439.1
|View full text |Cite
|
Sign up to set email alerts
|

Towards equality: gender representation at the Royal College of Radiologists’ Annual Scientific Meeting 2014-2021

Abstract: Background: Conferences facilitate career advancement, but gender imbalances in public fora may negatively impact both women and men, and society. We aimed to describe the gender distribution of presenters at the UK’s 2014-2021 Royal College of Radiologists’ (RCR) Annual Scientific Meeting. Methods: We extracted data on presenter name, role and session type from meeting programmes. We classified gender as male or female using names, records or personal pronouns, accepting the limitations of these categories. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For example, in their analysis of rates of question-asking in medical learning environments, Cromer et al (2022, p.1) found that, while "women had a lower rate of asking and answering questions… these disparities were attenuated in smaller, discussion-based and virtual classes." Similarly, in an analysis of the UK equivalent to the annual conference of radiology reported in Rezaee et al (2022), Gibson et al (2023) found that, while men dominated all conference participation roles during in-person events, "[t]he odds of roles being held by women increased during online meetings during COVID", leading them to conclude that "hybrid online/inperson formats may accelerate change." (p.1).…”
Section: Participation and Engagement In Conference And Related Eventsmentioning
confidence: 99%
“…For example, in their analysis of rates of question-asking in medical learning environments, Cromer et al (2022, p.1) found that, while "women had a lower rate of asking and answering questions… these disparities were attenuated in smaller, discussion-based and virtual classes." Similarly, in an analysis of the UK equivalent to the annual conference of radiology reported in Rezaee et al (2022), Gibson et al (2023) found that, while men dominated all conference participation roles during in-person events, "[t]he odds of roles being held by women increased during online meetings during COVID", leading them to conclude that "hybrid online/inperson formats may accelerate change." (p.1).…”
Section: Participation and Engagement In Conference And Related Eventsmentioning
confidence: 99%